Beanie the bansheenie - Colfer, Eoin; McCarthy, Steve, 1984- (Somerville, Massachusetts : Candlewick Press, 2024)
The sole job of a baby banshee, or 'bansheenie,' is to bond with a human and know all there is to know about that person, including when they're destined to breathe their last breath. One bansheenie named Beanie, however, is no ordinary herald of death. When she sees her person, a little girl named Rose, she decides to change both their fates--and instead of delivering bad news, protect Rose and her family. And when her banshee's howl won't work, she must draw power and strength from the ancient secrets and hidden networks of the natural world to create a new sound, a new way of being in the world, that will change everything.
Pub Weekly, September 2024
Kirkus Review, October 2024
K-3
Keywords: Banshees -- Juvenile fiction; Kindness -- Juvenile fiction; Friendship -- Juvenile fiction; Banshees -- Fiction; Kindness -- Fiction; Friendship -- Fiction